Osteoporosis and its relationship with sarcopenia in elderly patients - Bhuiyan, Faisal A.; Iqbal, Muhammad A.; Sherazul Islam, M.; Alam, Mohammad M.; Akther, Hasina; Jahangir Alam, M. (International Journal of Research in Medical Sciences, 2025)
Background: Osteoporosis and sarcopenia are two chronic conditions that are associated with aging and leading to an increase in bone fragility and fracture susceptibility. The objective of this study was to find out the relationship between osteoporosis and sarcopenia in elderly patients. Methods: This hospital-based cross-sectional descriptive study was conducted in the Department of Medicine, Cumilla Medical College Hospital, Bangladesh, from January 2020 to January 2021 in 100 elderly patients who are suffering from osteoporosis. Results: A total of 100 elderly osteoporotic patients were studied. The median age was 66±7, 88% females. Regarding different co morbidities diabetes mellitus (DM), hypertension (HTN), ischemic heart disease (IHD), dyslipidemia, osteoarthritis (OA) and chronic kidney disease (CKD), 31 (31%), 23 (23%), 7 (7%), 9 (9%), 21 (21%) and 5 (5%) respectively. Among 100 cases, 71 (71%) patients were osteoporotic and 29 (29%) patients were severe osteoporotic, where vertebral compression fracture, femoral neck fracture and both are 18 (18%), 6 (6%) and 5 (5%) respectively. Sarcopenia is more common in severe osteoporotic patient and that is 72.4%. Hand grip strength 17.76±5.94 kg in right hand and 16±5.71 kg in left hand. Appendicular skeletal muscle mass (ASMM) index was 5.39±0.86 kg/m2. Correlation of appendicular skeletal muscle mass (ASMM) index along with BMD of lumber spine (T-score) and BMD of femoral neck (T-score) were significant and the Pearson correlation coefficient were 0.264 and 0.356 respectively. Correlation between sarcopenia and osteoporosis was significant (p=0.008). Conclusion: There is an intimate relationship between osteoporosis and sarcopenia. The prevalence of sarcopenia is higher in severe osteoporotic patient. Both conditions are significantly correlated to each other.